Feminismo e construção de identidades femininas : as meninas, de Lygia Fagundes Telles - Ruela, Natália (2009)
The representation of the female characters Lorena, Ana Clara and Lia from Lygia Fagundes Telles's novel As Meninas [The Girls] (1973) is analysed. The representation of female bodies in the above-mentioned novel of the 1970s seemingly evokes stereotyped models based on the dominant patriarchal ideology and reproduced by gender technologies, such as the cinema and television, and even by literature. In fact, they seem to be models of the goddesses Hera, Athena and Aphrodite, hailing from classical times and passed on through the centuries. However, the writer's option for multiple points of view makes possible a wider concept of the female characters' individual traits. The characters' representations distance themselves from the goddesses' model and from traditional concepts when their traits and thoughts, unseen by the other, are reflected in personal discourse and in the stream of consciousness. With regard to methodology, current analysis lies between structuralism and post-structuralism since it turns back to the structural elements that foreground the novel - such as point of view and the Greek goddesses' typology, suggested by Pravaz (1981) - and, at the same time, to the context in which it inserts itself especially with regard to Feminism in which it is inscribed and foregrounded. The novel has been investigated through concepts based on Feminist Critical Theory. Results reveal the problematization of ready-made and fixed models that predetermine women's fixed roles and places. Lorena's, Ana Clara's and Lia's character construction indicate new methods related to the gender issue. In fact, the emblematic female models seek different places and significant changes related to their being in society. This may occur even when they frequently find themselves in situations which betray them and place them, unaware, in the place destined by traditional patriarchy in which they were constituted.